Insight into the Theory of Truth from the Lens of Five Review Articles - Wulandari, Farni; Lauren, Cendy; Resti Rahmadani, Anggi (Universitas Lancang Kuning, 2019)
As a central philosophical subject, the discourse of truth has existed for thousands of years. One of the most influential theories of truth is James & Katz (1975) book entitled “The Meaning of Truth.” This study aims to analyze the different views on the theory of truth from five articles that have reviewed the theory. This study used a descriptive qualitative method to review these five articles, which serve as the data that this study analyzed. The textual analysis identified and classified the different opinions of other researchers who have reviewed the theory in detail. Additionally, this paper also reviewed the strengths and weaknesses of these five review articles that served as a benchmark in reviewing the theory of truth.